91 Assessing Variability of Herd Sire Economic Value for Commercial Operations. (8th October 2021) - Dodd, Logan; Anderson, David; Riley, David G; Johnson, Barton; Herring, Andy D
Abstract: Number of calves (n = 596) and weaning calf value (n = 574) from natural service, multi-sire breeding groups were evaluated in a crossbred research herd. Sires and dams that were F1 crosses of Angus (A) and Nellore (N) were mated annually during 60 to 90-day breeding seasons to produce spring-born calves in 2009–2015. Numbers of sires used annually varied from 5 to 9; numbers of females exposed per bull ranged from 14 to 22 across years. Bulls were pastured together throughout the year as well as breeding seasons. Sires were identified based on calf DNA genotyping. Calf number, birth date, birth weight, weaning weight, and economic value were determined per bull annually. Calf value was based on weaning weight and reported prices for respective weaning dates. Calf prices were calculated separately for steers and heifers relative to 22.7 kg (50 lb) increments for corresponding weight class and year. Mixed model analyses were conducted that included fixed categorical effects of calf birth year, type of F1 sire (A-sired vs. N-sired), sire nested within type, calf sex, and the interaction of F1 sire type with calf sex. Covariates of Julian birth date and calf weaning age were included for birth weight and weaning weight, respectively. Large differences in calf numbers and performance (P < 0.05) were observed. Weaned calves produced annually per sire ranged from 0 to 48. Average annual calf performance per sire ranged from 28.4 to 50.8 kg for birth weight and 146.5 to 249.0 kg for weaning weight. Annual economic value per sire ranged from $0 to $30, 870 when considering half of each calf's value as attributed to the sire. Commercial producers should consider potential sire variability for calf numbers, birth date distribution, and ratio of female-to-male calves in combination with calf performance for economic assessments.